77.6k views
3 votes
Y" +2y' +17y=0; y(0)=3, y'(0)=17

User Deluan
by
5.3k points

1 Answer

3 votes

Answer:

The solution is
y(t)=e^(-t)(\cos 32t + ((5)/(8)) \sin 32t)

Explanation:

We need to find the solution of
y''+2y'+17y=0 with

condition
y(0)=3,\ y'(0)=17

This is a homogeneous equation with characteristic polynomial


r^(2)+2r+17=0

using quadratic formula
x=\frac{-b\pm \sqrt{b^(2)-4ac}}{2a}


r=\frac{-2\pm \sqrt{2^(2)-4(1)(17)}}{2(1)}


r=(-2\pm √(4-68))/(2)


r=(-2\pm √(-64))/(2)


r=(-2\pm 64i)/(2)


r=-1 \pm 32i

The general solution for eigen value
a \pm ib is


y(t)=e^(at)(A \cos bt + B \sin bt)


y(t)=e^(-t)(A \cos 32t + B \sin 32t)

Differentiate above with respect to 't'


y'(t)=-e^(-t)(A \cos 32t + B \sin 32t) + e^(-t)(-32A \sin 32t + 32B \cos 32t)

Since, y(0)=3


y(0)=e^(0)(A \cos(0) + B \sin(0))


3=(A \cos(0) +0)

so, A=1

Since, y'(0)=17


y'(0)=-e^(0)(3 \cos(0) + B \sin(0)) + e^(0)(-32(3) \sin(0) + 32B \cos (0))


17=-(3 \cos(0)) + (0 + 32B \cos (0))


17=-3 + 32B

add both the sides by 3,


17+3 = 32B


20= 32B

divide both the sides, by 32,


(20)/(32)= B


(5)/(8)= B

Put the value of constants in
y(t)=e^(-t)(A \cos 32t + B \sin 32t)


y(t)=e^(-t)((1) \cos 32t + ((5)/(8)) \sin 32t)

Therefore, the solution is
y(t)=e^(-t)(\cos 32t + ((5)/(8)) \sin 32t)

User Subdir
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.